2004
DOI: 10.1016/j.bbadis.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides of Vibrio cholerae

Abstract: An account of our up to date knowledge of the genetics of biosynthesis of Vibrio cholerae lipopolysaccharide (LPS) is presented in this review. While not much information is available in the literature on the genetics of biosynthesis of lipid A of V. cholerae, the available information on the characteristics and proposed functions of the corepolysaccharide (core-PS) biosynthetic genes is discussed. The genetic organizations encoding the O-antigen polysaccharides (O-PS) of V. cholerae of serogroups O1 and O139,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 100 publications
1
37
0
Order By: Relevance
“…WbdD is the terminating enzyme and thus regulates chain length by methylat-ing the glycan: the higher the concentration of this enzyme, the shorter the glycan chains (174). An ABC transporter formed by the Wzm-Wzt heterodimer transports the structure to the periplasm (63,150,(175)(176)(177) (Fig. 6B).…”
Section: Macroamphiphilic Glycolipidsmentioning
confidence: 99%
“…WbdD is the terminating enzyme and thus regulates chain length by methylat-ing the glycan: the higher the concentration of this enzyme, the shorter the glycan chains (174). An ABC transporter formed by the Wzm-Wzt heterodimer transports the structure to the periplasm (63,150,(175)(176)(177) (Fig. 6B).…”
Section: Macroamphiphilic Glycolipidsmentioning
confidence: 99%
“…It has been shown that the regions for O-antigen biosynthesis in V. cholerae O1, O22, O31, O37, and O139 are surrounded by gmhD and rjg genes and that this region is also important for the production of capsule of non-O1 V. cholerae O31 and O139 (7,10,11,12). In the V. anguillarum serotype O1 strain, virA (wbhS) and virB (wbhR) are involved in LPS biosynthesis and have been shown to be important for virulence (53).…”
Section: Fig 3 Genomic Islands Of Strain 775 Predicted By Islandviementioning
confidence: 99%
“…Strains exhibit extensive phenotypic and genetic heterogeneity and can be classified according to several different criteria. For example, serogroup designation is based on the structure of the somatic O antigen, whereas the pathogenicity of a strain is determined by its ability to colonize a human host and cause the severe and potentially lethal diarrheal disease known as cholera (15,26,68). Importantly, more than 200 different serogroups have been identified, and both pathogenic and nonpathogenic strains of different serogroups have been found to coexist in environmental reservoirs worldwide (27,77).…”
mentioning
confidence: 99%